RAMANUJA AND AL-GHAZALI - Siddiqi, Muzammil H (Journal of Dharma, 1981)
Monotheism and monistic theism are two very distinct and different terms. On the philosophical and theological level they could be called mutually contradictory. In the one, monotheism, there is an affirmation of one absolute being who is worthy to be called God or Theos, and everything else stands in relation to God as subordinate, separate and dependent—for its very existence. Monistic theism is, on the other hand, less clear on this issue. It does not make such a sharp distinction between Creator and creature. It rather speaks of the oneness of being, and then either denies being and reality to other things or subsumes all and everything that exists in one Being who is their ground and source. On the experiential level, however, these two diverse and different positions can meet and interact.